THE EFFECTIVENESS OF VISUAL AID IN IMPROVINGSTUDENTS' LISTENING ABILITY:A CLASSROOM ACTION RESEARCH AT SECOND GRADE OF SMAN 2 CIMAHI - Riska Marliana Suhendi, - (2009)
The lack of awareness to develop it because second learners think it is hard to improve it. This study examines the effectiveness of visual aid in improving students' listening ability. This study involves 72 students in the second grade of SMAN 2 Cimahi 2009. This research was using quantitative analysis to compute the data from pre-test and post-test. A questionnaire also distributed to gain students' perception toward visual aid usage in improving their listening ability. The study found that the experiment group has tobt (13.066) higher than tcrit (2.042) at the level 0.05. In the other hand, the control group has tobt (-0.686) lower than tcrit (2.042) at the level 0.05. It means that the visual aid strategy is effective in improving students' listening ability. Based on the questionnaire, picture as visual aid has good influence to improve listening ability. The students also said that they got new vocabularies and knew how to pronounce some words correctly according to the stress and the intonation. Pictures can make students understand better the meaning in listening because they have the visual of the dialogue. For that reason, this study suggests the use of visual aid in teaching listening to students.